The Distortion of Upward Communication in Hierarchical Organizations - Athanassiades, John C. (Academy of Management Journal, 1973)
Distortion of upward communication by subordinates is viewed as instrumental for attainment of need-goals. The study investigates relationships between distortion of upward communication, needs of subordinates, and aspects of organizational climate. Distortion of upward communication is negatively related to level of security and positively related to achievement needs; also positively related to a ?heteronomous? organizational climate and negatively related to an ?autonomous? climate.